Positive aspects of caregiving among informal caregivers of persons with dementia in the Asian context: a qualitative study - Yuan, Qi; Zhang, Yunjue; Samari, Ellaisha; Jeyagurunathan, Anitha; Goveas, Richard; Ng, Li Ling; Subramaniam, Mythily (BMC geriatrics, 2023)
Background Positive aspects of caregiving are important coping resources for informal caregivers of persons with dementia (PWD). However, existing studies mostly focused on caregivers from western societies and less attention was paid to the potential cultural differences. This study aims to explore positive aspects of caregiving in the Asian context. Methods A qualitative methodology with semi-structured interviews was adopted. A total of 29 informal caregivers of PWD in Singapore were interviewed from Apr 2019 to Dec 2020. All the interviews were audio-recorded and transcribed verbatim for the analysis. Inductive thematic analysis was conducted. Results The results revealed a total of three major themes with 11 sub-themes including: 1) positive aspects within self (i.e., better understanding of dementia and caregiving, personal growth, role satisfaction, and improved awareness of self-care); 2) positive aspects between caregiver and PWD (i.e., chance to demonstrate filial piety towards PWD, happiness and positive attitudes of PWD, positive interactions with PWD, and closer relationships with PWD); and 3) positive aspects between caregiver and others (i.e., empathy towards other caregivers, befriending peers, and sharing dementia and caregiving knowledge with others). Discussion Findings from this study improved our understanding on positive aspects of caregiving among informal caregivers of PWD in the Asian context. In addition to similar themes across cultures such as personal growth, our study identified a few unique themes like improved awareness of self-care and chances to demonstrate filial piety. For future studies targeting Asian caregivers, it is necessary to include these cultural-specific positive aspects of caregiving.